2015
DOI: 10.4238/2015.october.29.28
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regulatory T cell subsets in the peripheral blood of immunoglobulin A nephropathy (IgAN) patients

Abstract: ABSTRACT. The aim of this study was to investigate the clinical significance of regulatory T cells (Tregs) and its subsets in immunoglobulin A nephropathy (IgAN) patients. Peripheral blood samples of 20 IgAN patients and 20 healthy individuals of similar ages were analyzed. Levels of Tregs and its subsets, namely nTregs and iTregs, were analyzed using flow cytometry. The number of Tregs in IgAN patients was significantly lower than that in the healthy controls. While significant reduction in iTregs primarily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…However, the nTreg levels did not significantly change. In addition, the expression levels of TGF-β and IL-10 in patients with IgAN were lower, whereas those of IL-17 were higher compared with that in healthy controls (81). Furthermore, in a study of 35 patients with IgAN and 35 patients without renal disease, CD4 + CD25 + Treg cells were significantly lower in patients with IgAN compared with that in the controls before tonsillectomy, and were also negatively correlated with blood urea nitrogen, IL-4 levels and proteinuria, positively correlated with eGFR, and gradually decreased as the severity of renal histology increased.…”
Section: Tregsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the nTreg levels did not significantly change. In addition, the expression levels of TGF-β and IL-10 in patients with IgAN were lower, whereas those of IL-17 were higher compared with that in healthy controls (81). Furthermore, in a study of 35 patients with IgAN and 35 patients without renal disease, CD4 + CD25 + Treg cells were significantly lower in patients with IgAN compared with that in the controls before tonsillectomy, and were also negatively correlated with blood urea nitrogen, IL-4 levels and proteinuria, positively correlated with eGFR, and gradually decreased as the severity of renal histology increased.…”
Section: Tregsmentioning
confidence: 83%
“…Immunohistochemistry analysis of IgA revealed that the deposition of IgA in the mesangial cells was lower compared with that in a rat IgAN model (80). Yang et al (81) demonstrated that the number of iTregs in patients with IgAN was significantly lower compared with that in healthy controls. However, the nTreg levels did not significantly change.…”
Section: Tregsmentioning
confidence: 99%
“…Of note, IL-17A can induce the production of pro-inflammatory cytokines such as TNF and IL-1 from endothelial cells and infiltrating macrophages [53]. The important role of IL-17 and Th17 cell in renal inflammation is suggested in glomerular vasculitis including lupus nephritis, ANCA-associated vasculitis, and IgAN [54,55].…”
Section: Role Of Fractalkine/cx3cr1 Interaction In Iganmentioning
confidence: 99%
“…Glomerular IgA immune complex deposition triggers innate immune responses and subsequent T‐cell activation and inflammation. In patients with IgA nephropathy, there may be an imbalance of Tregs and Th17 cells in the periphery and in renal tissues, with a lower frequency of CD45RA − Foxp3 hi ‐activated Tregs and an increase in Th17 cells . These differences are associated with reduced levels of serum IL‐10 and increased levels of serum and urine IL‐17A in IgA patients .…”
Section: Regulatory T Cells In Autoimmune Glomerulonephritismentioning
confidence: 99%
“…58,59 These differences are associated with reduced levels of serum IL-10 and increased levels of serum and urine IL-17A in IgA patients. 58,59 Furthermore, the altered distribution of Tregs and Th17 cells correlates with prognostic indicators such as impaired GFR, proteinuria, tubulointerstitial injury and hypertension. 58 Functionally, a small study in rats with IgA nephropathy suggests that the adoptive transfer of CD4 + CD25 + Tregs, expanded in vitro, reduces proteinuria and possibly IgA deposition, hyperplasia of glomerular mesangial cells and tubular epithelial damage.…”
Section: Iga Nephropathymentioning
confidence: 99%